PENGARUH WORK LIFE BALANCE, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BIRO UMUM SEKDA PEMPROV JATIM - Elfania Prenzi Andhira,; Daffa Abdi Prasetya,; Amara Lintang Adani,; Eko Tjiptojuwono, (Journal of Innovation Research and Knowledge, 2025)
Employee productivity plays an important role in determining the success of an institution, especially in government agencies such as the General Bureau within the Regional Secretariat of East Java Province. This study was designed to evaluate the impact of work-life balance, work motivation, and employee satisfaction levels on staff performance. A quantitative method was employed through a survey of 39 permanent employees. Data were analyzed using multiple linear regression with classical assumption tests (normality, multicollinearity, heteroscedasticity). Results revealed that work the analysis results showed that work enthusiasm had a significant impact on performance (β=0.893; p=0.000). Meanwhile, work-life balance (p=0.249) and job satisfaction (p=0.406) did not have a significant impact the findings reinforce motivation as the primary driver of bureaucratic performance while challenging conventional assumptions about WLB and job satisfaction. Practically, organizations should prioritize evidence-based policies to enhance intrinsic motivation. Further research should explore mediating variables such as organizational culture.